Expanding options to include language barriers for predicting postoperative delirium in geriatric patients. Issue 1 (17th October 2022) - Streetman, Daniel; Hagley, Alana; Shalom, Moshe; Gendreau, Julian L.
Abstract : See the Reply by Chary et al . in this issue.